(untitled) (Research, Society and Development, 2020)
Among current methods, landfill is the most used - and least harmful according to the National Solid Waste Policy - for final disposal of Urban Solid Waste (MSW) with engineering techniques to control the waste components in the system. Leachate, resulting from the biodegradation of organic matter, is a highly contaminating liquid and an environmental challenge regarding its treatment. For the realization of the study, data were collected, for nine years, from the Landfill of Maceió assessing the behavior of the leachate parameters. The study consisted of evaluating the environmental parameters in their concentrations, the flow of the leachate generated and its correlation with precipitation. The values found showed that the landfill presents great variability in the concentrations of its parameters over time, mainly of Biochemical Demand and Oxygen (DBO) and Chemical Oxygen Demand (COD), which showed higher concentrations in rainy periods. The leachate flow increased in rainy periods, confirming the influence of precipitation. Ammoniacal Nitrogen, pH and Alkalinity did not show any influence of precipitation, being more related to the anaerobic degradation phase of the landfill, which currently tends to be in the methanogenic phase.